Two-phase optimal path planning of autonomous ground vehicles using pseudo-spectral method. (December 2014) - Mashadi, Behrooz; Majidi, Majid
In this paper, an optimal path-planning method is proposed for autonomous ground vehicles in case of overtaking a moving obstacle by the application of a two-phase optimal-control problem. When the autonomous vehicle detects a moving vehicle in a proper speed and distance ahead, it decides to overtake the obstacle by executing a double-lane change manoeuvre. The path for the overtaking manoeuvre is generated by a two-phase optimal path-planning problem. The cost function of the first phase is defined in such a way that the vehicle approaches the obstacle as close as possible. In the second phase, the cost function is defined as sum of the vehicle lateral deviation from the reference path and the rate of steering angle. At the same time, the lateral acceleration of the vehicle must not exceed a specified limit. The radio pseudo-spectral method, which is a method for direct trajectory optimization using global collocation at Legendre–Gauss–Radau points, is applied for solving the two-phase nonlinear optimal-control problem. A full nonlinear vehicle model in CarSim software is used for path-tracking simulation by importing path data from a MATLAB code. The simulation results show that the generated path for the autonomous vehicle satisfies all vehicle-dynamics constraints and hence is applicable for a real autonomous vehicle.